Predisposing factors and prognosis of status epilepticus in patients with autoimmune encephalitis. Issue 13 (March 2020) - Zhang, Yu; Deng, Chen; Zhu, Lina; Ling, Liu
Abstract : Abstract: The aim of this study was to study the predisposing factors and prognosis of status epilepticus (SE) in patients with autoimmune encephalitis (AE). A total of 227 cases of AE were collected from the inpatient department of West China Hospital of Sichuan University from January 2010 to May 2018. All patients met the 2015 criteria for the diagnosis of AE. The binary logistic regression model was used to multivariate and retrospective chart analysis the predisposition factors for SE and its prognostic factors. Of the 227 patients with AE, 50 (22.03%) had SE during hospitalization, and 19 patients with SE had a poor prognosis (modified Rankin score MRS = 3–6), and 7 patients with no SE had a poor prognosis. In the logistic regression model, electroencephalograms (EEGs) abnormalities ( P  = .000) and head magnetic resonance imaging (MRI) abnormalities ( P  = .003) were associated with a predisposition to SE, while Glasgow scores <8 ( P  = .027), abnormal EEG ( P  = .046), delayed immunotherapy ( P  = .012), and SE duration at admission lasting >30 minutes ( P  = .023) were risk factors for a poor prognosis of SE. SE is a common complication in patients with AE. EEG and MRI abnormalities may be predisposing factors for SE. Glasgow scores <8 points, abnormal EEG, delayed immunotherapy, and SE duration lasting >30 minutes at admission are risk factors for a poor prognosis in patients with SE.